Psychosocial interventions following self-harm in adults: a systematic review and meta-analysis. - Hawton, K; Witt, K; Salisbury, T; Arensman, E; Gunnell, D; Hazell, P; Townsend, E; van Heeringen, K (Lancet, 2016)
Background Self-harm (intentional acts of non-fatal self-poisoning or self-injury) is common, particularly in young adults aged 15–35 years, often repeated, and strongly associated with suicide. Effective aftercare of individuals who self-harm is therefore important. We have undertaken a Cochrane systematic review and meta-analysis of the effectiveness of psychosocial interventions for self-harm in adults. Methods We searched five electronic databases (CCDANCTR-Studies and References, CENTRAL, MEDLINE, Embase, and PsycINFO) between Jan 1, 1998, and April 29, 2015, for randomised controlled trials of psychosocial interventions for adults after a recent (within 6 months) episode of self-harm. Most interventions were assessed in single trials. We report results for interventions for which at least three randomised controlled trials comparing interventions with treatment as usual have been published and hence might contribute to clinical guidance. The primary outcome was repetition of self-harm at the conclusion of treatment and at 6, 12, and 24 months' follow-up analysed, when available, with the intention-to-treat method; if this was not possible, we analysed with all available case data. Findings We identified 29 non-overlapping randomised controlled trials with three independent trials of the same intervention. Cognitive-behavioural-based psychotherapy (CBT; comprising cognitive-behavioural and problem-solving therapy) was associated with fewer participants repeating self-harm at 6 months' (odds ratio 0·54, 95% CI 0·34–0·85; 12 trials; n=1317) and at 12 months' follow-up (0·80, 0·65–0·98; ten trials; n=2232). There were also significant improvements in the secondary outcomes of depression, hopelessness, suicidal ideation, and problem solving. Patients receiving dialectical behaviour therapy (in three trials) were not less likely to repeat self-harm compared with those provided with treatment as usual at 6 months (odds ratio [OR] 0·59, 95% CI 0·16–2·15; n=267, three trials) or at 12 months (0·36, 0·05–2·47; n=172, two trials). However, the secondary endpoint of frequency of self-harm was associated with a significant reduction with use of dialectical behaviour therapy (mean difference −18·82, 95% CI −36·68 to −0·95). Four trials each of case management (OR 0·78, 95% CI 0·47–1·30; n=1608) and sending regular postcards (OR 0·87, 95% CI 0·62–1·23; n=3277) did not reduce repetition of self-harm. Interpretation CBT seems to be effective in patients after self-harm. Dialectical behaviour therapy did not reduce the proportion of patients repeating self-harm but did reduce the frequency of self-harm. However, aside from CBT, there were few trials of other promising interventions, precluding firm conclusions as to their effectiveness.